In-person and telemedicine course models for disaster preparedness: a comparative analysis - DORIGATTI,ALCIR ESCOCIA (2018)
ABSTRACT Objective: to compare the students’ performance in face-to-face and telemedicine courses for the training and necessary action in disasters, using telemedicine as an effective training tool. Methods: online research conducted after the end of the course of preparation in disasters, carried out in-person, as well as by videoconference. We compared the performance of students in the in-person course and through telemedicine. Results: in the comparison of the results obtained with the pre- and post-test data between the students who attended via telemedicine and in-person, we observed that in the two modalities there was an increase in knowledge (p<0.001). We also observed no statistically significant differences in the posterior evaluation between the in-person and telemedicine courses (p=1.0), however, there was a significant difference at the pre-test evaluative moment (p<0.001). Conclusion: videoconferencing can be effectively used to train health professionals in disaster management, being able to provide adequate knowledge and become an important tool to distance reaching in continuing education.